Enhanced angiotensin II induced sodium appetite in renovascular hypertensive rats - Roncari, Camila F. [UNESP]; Barbosa, Rafaela M. [UNESP]; Vendramini, Regina C. [UNESP]; De Luca, Laurival A. [UNESP]; Menani, José V. [UNESP]; Colombari, Eduardo [UNESP]; Colombari, Débora S.A. [UNESP] (Elsevier, 2018)
Renovascular hypertensive 2-kidney, 1-clip (2K1C) rats have an increased activity of the renin-angiotensin system and an initial transitory increase in daily water and NaCl intake. However, the dipsogenic and natriorexigenic responses to angiotensin II (ANG II) have not been tested yet in 2K1C rats. Therefore, in the present study, we evaluated water and 0.3 M NaCl intake induced by water deprivation (WD)-partial rehydration (PR) or intracerebroventricular (icv) ANG II in 2K1C rats. In addition, the cardiovascular changes to these treatments were also evaluated. Male Holtzman rats received a silver clip around the left renal artery to induce 2K1C renovascular hypertension. In the 5th week, a group of animals received a guide cannula in the lateral ventricle for icv injections. Daily water intake increased from the 3rd week after surgery and remained elevated until the 6th week (last recording week), whereas daily 0.3 M NaCl intake transiently increased from the 2nd to the 5th week after surgery. On the 6th week, in spite of comparable daily 0.3 M NaCl intake between 2K1C and sham rats, WD-PR and icv ANG II induced an increased 0.3 M NaCl intake in 2K1C rats. Water intake induced by WD-PR, not by icv ANG II, also increased in 2K1C rats. The increase in arterial pressure to WD-PR or icv ANG II was similar in sham and 2K1C rats. Therefore, these results suggest that 2K1C rats are more responsive to the natriorexigenic effects of ANG II, whereas other responses to ANG II are not modified.
Keywords: 2K1C; Angiotensin; Dehydration; Hypertension; Sodium intake